Perceptions of evidence-based practice among Vietnamese psychology students - Nguyen-Thi, My-Tien; Nguyen, Vu Hoang Anh; Luu-Thi, Huyen-Trang; Tran-Chi, Vinh-Long (Journal of Asian Scientific Research, 2023)
Evidence-based practice in psychology (EBPP) improves public health and makes it easier for psychologists to do their jobs well by using case formulation, intervention, and therapeutic relationship principles that have been shown to work in the real world. The utilization of evidence-based practice in the field of psychology has been widely regarded as the most effective approach for researchers and practitioners to incorporate current data into their therapeutic practice and decision-making processes. The objective of this study was to investigate attitudes towards EBPP and assess the level of exposure to evidence-based practice and evidence-based therapies in the corresponding training program among students. A cohort of 250 undergraduate students pursuing a degree in psychology were enlisted to participate in the survey. The research employed quantitative methodologies, specifically one-way ANOVA, Pearson correlation, and regression analysis, to examine and interpret the collected data. The favorable influence of students’ judgments of the sufficiency of training in different components of clinical expertise and exposure to evidence-based practice (EBP) and evidence-based treatments (EBTs) in their respective training program can be observed in students’ experiences and attitudes towards EBP in psychology. The findings derived from the present study provide compelling evidence supporting the imperative of implementing educational interventions aimed at enhancing the research knowledge and skills of psychology students, as well as their ability to effectively utilize research in their academic pursuits.